The Dark Side of Leadership: Does Boldness Predict Successful Interpersonal Behaviors? (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
“Successful psychopaths“ display psychopatic personality traits (i.e. lying, manipulating) in businness environments but do not display deviant lifestyles. The Triarchic Psychopathy Model proposed that psychopathy encompasses three phenotypic constructs: boldness, meanness and disinhibition. In line with theoretical assumptions, boldness is adaptive component of psychopathy and can therefore be useful for identifying “successful“ expressions of psychopathy. The aim of this research was to investigate whether boldness added incrementally in predicting emotional intelligence. Data was collected on 495 students (252 male) using the Triarchic Psychopathy Measure (TriPM, Patrick, 2010), and Wong and Law Emotional Intelligence Scale (WLEIS, Wong et al., 2002). Hierarchical regression analysis showed that boldness did add incrementally to meanness and disinhibition in accounting for variance in total WLEIS score (12%), Self-emotional appraisal (5%), Others' emotional appraisal (2%), Use of emotion (14%) and Regulation of emotion (6%). Results of this study indicate that boldness has adaptive potential and represent a helpful factor for successful interpersonal behaviors such as EI.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.